A) If only conclusion I follows | B) If only conclusion II follows |

C) If neither I nor II follows | D) If both I and II follow |

Explanation:

I is not hinted at. It is an invention of the concluder's mind. II follows because if "the whole purpose of something is defeated", it loses its meaning.

A) Only Conclusion I is true | B) Only Conclusion II is true |

C) Both conclusions I & II are true | D) Neither conclusion I nor II is true |

Explanation:

From the given Statements :

1. I > W > T > N

2. F = G = C

Conclusions are :

I. W > I (False)

II. C > N (True)

A) Only 3 | B) Both 2 & 3 |

C) Any two of (1, 2 & 3) | D) None |

Explanation:

Using Both 1 & 2 statements we get the rate of interest as in (1) we have given principle amount and in (2) compound interest for 2 years. By this data we get the rate%.

Using Both 1 & 3 statements we can get the rate% as we have principle amount & difference between compound interest and simple interest in 2 years.

Using Both 2 & 3 statements we get compound interest & simple interest by which we get principle amount. So that we can calculate %rate.

Hence by using any two of the three statements(1,2&3) we get rate of interest.

A) Only A follows | B) Only B follows |

C) Both (A) and (B) follows | D) Neither (A) nor (B) follows |

A) a >= b | B) a <= b |

C) a < b | D) a > b |

Explanation:

1.

5a(a-3)-3(a-3) = 0

(5a-3)(a-3) = 0

a = 3 or 3/5

2.

3b(b+2)-1(b+2) = 0

b = -2 or b = 1/3

Here when a = 3, a > b for b = -2 and b = 1/3

when a = 3/5. a > b for b = -2 and b = 1/3.

Hence it is clesr that a > b.

A) only conclusion B is true. | B) only conclusion A is true. |

C) neither conclusion I nor II is true. | D) either conclusion I or II is true. |

Explanation:

From given statements, we can conclude that

**N > C < T < L= P > Q** .....(1)

Here given that **C > Y** but in eq(1) we got that **C < T < T <= P** => Y is definitely less than P.

So only conclusion B is True.